Students’ Difficulties in Writing Paragraph at Tenth Grade of SMKS Pembina Bangsa - Ratma Deli; Arifmiboy Arifmiboy (Journal of English Language and Education, 2021)
This research was aimed to discover students’ difficulties in writing a paragraph in tenth grade. It was done at SMKS Pembina Bangsa Bukittinggi. The researcher found some phenomenon’s that faced students with the difficulty in writing; the students had a lack of vocabulary, some students had difficulty in finding and expressing the ideas, and low motivation in writing. The purpose of the research is to know the level of students’ difficulties in writing the paragraph. The design of this research was a survey. The population and sample of this research were the students at the tenth TKJ class of SMKS Pembina Bangsa Bukittinggi. Technique sampling of this research was the total sampling technique. The number of students was 30 students. The instrument that has been used is a questionnaire. Technique analysis of the data was collected, tabulated, calculated, found the mean, categorizing the data, and making the conclusion. N Based on the finding and analysis of the data of this research, the researcher found some problem that faced by student in writing a paragraph, the level of difficulties was “high” with 83,04%, with the interpretation of the data ≥ 70% - ≤ 90%.